Biochemical composition of amniotic fluid in normal puppies at term of pregnancy: preliminary data (International Journal of Health, Animal Science and Food Safety, 2017)
The full knowledge of the normal fetal fluids composition could be useful in the dog for the better management of newborns. The aim of the present study was to define the biochemical composition of amniotic fluid of puppies born by elective Caesarean section (CS) at term of pregnancy. The study enrolled 24 purebred bitches, classified into small size (20kg). All the bitches were healthy and clinically monitored from mating until parturition. For all the bitches an elective CS at term of pregnancy was performed [1]. For each puppy, the amniotic fluid was collected, immediately centrifuged and frozen at – 20° C until analysis for ALB, AMY, TB, CHOL, CK, ALP, GGT, AST, ALT, LDH, Mg, Ca, K, Na, Trig, BUN, Glc, TP, CREA, LIP, Cl, and GLOB. Data were analyzed by ANCOVA to verify the possible effects of parity, breed body size and newborn gender on amniotic biochemical composition. A total of 69 amniotic fluid samples were collected. The amniotic mean±SD and min-max values for each parameter were defined. LDH (p
Keywords: dog; neonate; fetal fluids; biochemical composition